Corpus callosum thinning in autosomal dominant hereditary spastic paraplegia associated with a novel TUBβ4A mutation. Issue 4 (28th July 2020) - Lamartine S. Monteiro, Marta; Vandernoot, Isabelle; Desmyter, Laurence; Wermenbol, Vanessa; Naeije, Gilles; Remiche, Gauthier
Abstract : Siblings with hereditary spastic paraplegia and corpus callosum thinning associated with a novel TUBβ4A mutation.